If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -12 + -4y + 8 = 0 Reorder the terms: -12 + 8 + 7y + -4y = 0 Combine like terms: -12 + 8 = -4 -4 + 7y + -4y = 0 Combine like terms: 7y + -4y = 3y -4 + 3y = 0 Solving -4 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = 0 + 4 3y = 0 + 4 Combine like terms: 0 + 4 = 4 3y = 4 Divide each side by '3'. y = 1.333333333 Simplifying y = 1.333333333
| 24v^4+30v^3b^2-21v^2b^2= | | 5(6+6X)=60 | | 15-6y=1-4y | | 0.5s=4s*21 | | 8n+9(n+3)= | | 8n+9= | | 6x-4=6(x-1) | | 0.67(6x-9)=x+5 | | -8x^2(-17x^2+46)= | | 0.25x+y=4 | | 15(x-8)=x+2-(2x+5) | | w^2-3w+2= | | 5(x-8)=x+2-(2x+5) | | -6(v+2)+3v+6=6v+7 | | (4x+6y+9)(4x+6y-9)= | | 4r=22 | | 6x-10=6(x-2) | | -2(8p+2)-3(2-7p)-2(4+2p)=0 | | 4v-10-4v=5 | | 6(4-5X)=234 | | (2x+13)(2x+13)=8 | | (9x+1)(9x-1)= | | 5(-6X-7)=145 | | 16t^2+84t= | | 5(1+4y)=2(3+10y) | | 2(2-x)-(4-x)=-5 | | 2.5a-6=1.12a-1.86 | | x^2-15+x^2-36= | | 9(x+12)-4x=143 | | -3(w+5)+7=-23 | | 3x+1-5(x+1)=6x+3 | | -7(-6X-2)=-448 |